Solubility of Zirconia-Based Ceramic Composite Resin After Immersion in Lemon Juice (Citrus limon (L.) Burm.) - Afrida Nurmalasari; Essie Octiara; Dewi Shafira (TALENTA, 2025)
Zirconia-based ceramic composite resin is a restorative material with high mechanical strength and aesthetic properties, but its solubility in acidic environments remains a concern. Acidic beverages, such as lemon juice (Citrus limon (L.) Burm.), contained citric and ascorbic acids, which could compromise stability in the oral cavity. Therefore, this study aimed to evaluate solubility of zirconia-based ceramic composite resin after immersion in lemon juice. Methods: This laboratory experimental study used a post-test only control group design with 24 zirconia-based ceramic composite resin discs (2 mm thick, 8 mm diameter). Samples were divided into three groups, namely control (immersed in distilled water for 24 hours), as well as immersion in lemon juice for 12 hours and 24 hours. Solubility was measured by weight difference before and after immersion using an analytical balance and calculated with Oysaed & Ruyter’s formula. The collected data were analyzed using the Shapiro–Wilk and Levene tests, followed by Kruskal–Wallis and Mann–Whitney tests. The mean solubility was 0 µg/mm³ in the control group, 0.00018 µg/mm³ in the 12-hour lemon juice group, and 0.00052 µg/mm³ in the 24-hour lemon juice group. Statistical analysis showed significant differences among groups, as evidenced by p < 0.05. Conclusion: Immersion in lemon juice increased solubility of zirconia-based ceramic composite resin. Solubility values were higher with longer immersion time, Keywords: solubility, zirconia-based composite resin, lemon juice, Citrus limon, acidic beverages